KEARIFAN LINGKUNGAN DALAM BUDAYA MASYARAKAT SEBAGAI SUMBER PEMBELAJARAN PADA DIKLAT GURU IPS MADRASAH TSANAWIYAH - Yoyo Supriono (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
Inheritance of local cultural values through formal education is an effort to prevent the entry of negative effects of globalization. For this reason, it is necessary to study which local values are worthy of being used as learning resources and to examine the effect of these learning resources on improving the quality of learning outcomes. Environmental wisdom as one of the cultural values that thrives in society has been able to make the natural environment remain sustainable. Environmental sustainability is certainly not only the needs of the education community, but the needs of all humanity. For this reason, institutionalizing local values is a non-negotiable need. Thus, the value of local culture, especially environmental wisdom is very important to make social studies more meaningful. The important meaning of learning resources for environmental wisdom in social studies education is that it can increase students' interest and learning passion and teachers as educators no longer make books and themselves as the most important learning resources so that they can cover their weaknesses.  Key words: Environmental Wisdom as Learning Resources